Seuils juridiques d’âge : du droit romain aux droits de l’enfant - Dominique Youf (Sociétés et Jeunesses en Difficulté)
Beyond the obvious disorder, the legal age threshold has been structured throughout history around three ideal rights types: the right to social order, the right to child protection and the right to Human Rights. The most representative example of the right to social order is Roman law. In this fundamentally holistic law, the child is not a subject of the law but is more the property of its father, the guarantor of familial order. However, towards the end of the Roman empire, the [premises] of the right to child protection and human rights began to appear for children.  These rights began to develop in earnest with [the modern project] at the end of the 19th century and especially in the 20th century.  The dynamic of the right to child protection involved the imposition of age thresholds in order to allow children the time to become autonomous adults.  Contrary to this, human rights tended to lower the age threshold in order to emancipate adolescents from their parent's guardianship more quickly. In order to avoid the return of the right of social order which has dominated for some years the reforms to the penal law of minors, it is imperative that we [put in place] a veritable Code for Children.